The Relationship between Work Stress and Work Performance of Debt Collection in Nonthaburi Province - สิงห์โต ปวริศ; อินฟ้าแสง อาภรณีน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aimed to: 1) examine the level of work-related stress among debt collection officers in Nonthaburi province, 2) assess the level of work performance of debt collection officers in Nonthaburi province, and 3) explore the relationship between work-related stress and work performance of debt collection officers in Nonthaburi province. The sample consisted of 400 debt collection officers from Nonthaburi province, and a questionnaire was used as the research tool. The results of the study revealed that: 1) the overall level of work-related stress among debt collection officers in Nonthaburi province was found to be at a high level. When examining the factors, the aspect of interpersonal relationships had the highest mean score, indicating that this factor had the greatest impact on work-related stress, 2) the overall level of work performance among debt collection officers in Nonthaburi province was rated as high. When broken down by aspect, the factor of work volume had the highest mean score, indicating the most favorable assessment in terms of work quantity, and 3) there was a very strong and statistically significant positive correlation between work-related stress and work performance of debt collection officers in Nonthaburi province at the 0.01 level of significance.